2020
DOI: 10.1002/ece3.6238
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the soil seed bank of giant ragweed and its significance in preventing and controlling its invasion in grasslands

Abstract: Giant ragweed (Ambrosia trifida, L. henceforth referred to as GR), an annual non‐native invasive weed, may cause health problems and can reduce agricultural productivity. Chemical control of GR in grasslands may have irreversible side effects on herbs and livestock. In an attempt to propose a solution to the harmful effects of GR on grasslands, this study explores the fate of its soil seed bank (SSB) and considers the physical control of its SSB reduction. By studying GR distributed in grasslands of the Yili V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It is newly recorded that giant ragweed invades grassland and causes serious damage. Through previous studies (Dong et al 2020) and this study, it was found that a large number of seeds are produced every year, which is an important reason why giant ragweed can cause damage to the grassland. With the increase in invasion years, a dense forest population was formed in the aboveground portion of the studied ecosystem.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…It is newly recorded that giant ragweed invades grassland and causes serious damage. Through previous studies (Dong et al 2020) and this study, it was found that a large number of seeds are produced every year, which is an important reason why giant ragweed can cause damage to the grassland. With the increase in invasion years, a dense forest population was formed in the aboveground portion of the studied ecosystem.…”
Section: Discussionmentioning
confidence: 58%
“…However, more than 98.66% of its seeds are consumed in one year, and a few of them are actually used for germination (Dong et al 2020). Therefore, it can be said that the high seed bank density generated in that year is the basis for the formation of a dense population of giant ragweed in the following year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations